(untitled) (Journal of Mechanical Engineering, 2011)
Shipbuilding is considered to be a thrust sector in the economy of Bangladesh. But various problems are there to obstruct the development of this sector. This paper is aimed to identify the underlying problems and then analyze the nature of the problems to make it helpful overcoming the obstacles. A brief history and prospect of the shipbuilding industries in Bangladesh in the perspective of global scenario is also discussed. DOI: http://dx.doi.org/10.3329/jme.v41i2.7509